P108 Anti-nerve growth factor (anti-NGF) antibodies as analgesia in the management of osteoarthritis. (26th April 2021) - Rammanohar, Jashmitha; Sutton, James; Seah, K T Matthew; Khan, Wasim S; To, Kendrick
Abstract: Background/Aims   Osteoarthritis is a major cause of morbidity and disability. Much of this comes from joint pain, which is exacerbated by movement and exercise. Pharmacological analgesia therefore not only has the obvious benefit of alleviating pain, but in doing so, it also facilitates exercise (a pillar of conservative management). Non-steroidal anti-inflammatory drugs (NSAIDs) and opioids are currently the main analgesics used in this context. However, these agents can cause unwanted side effects and are contraindicated in some patients. We thus conducted a systematic review and meta-analysis using the Cochrane collaboration criteria to evaluate the efficacy of anti-nerve growth factor (anti-NGF) antibodies as potential alternative analgesics in osteoarthritis of the hip and/or knee. Whilst tanezumab has been studied extensively and monoclonal anti-NGF antibodies have been reviewed in other pain states, this is the first systematic review of three key anti-NGF antibodies: tanezumab, fulranumab and fasinumab in symptomatic hip and/or knee osteoarthritis. Methods   An interdisciplinary work group conducted a literature search across seven electronic databases for the use of anti-NGF antibodies in osteoarthritis. All hip/knee osteoarthritis studies investigating anti-NGF antibodies regardless of dose regimen or phase of trial were included. Studies in which participants received NSAIDs or analgesics other than anti-NGF antibodies, or studies in which the only intervention was the administration of anti-NGF antibodies in combination with NSAIDs or other analgesics were excluded. The Jadad Scale score was used to assess the quality of each study. Results   Thirteen studies involving 8, 145 patients with a diagnosis of hip and/or knee osteoarthritis were analysed. Demographic information including duration of disease and Kellgren-Lawrence grades were also extracted. Anti-NGF antibodies showed significant improvements compared to placebo as rated on the Western Ontario and McMaster Universities Arthritis Index (WOMAC) scales for pain (SMD= -0.50, 95% CI -0.71 to -0.28, P < 0.00001; I 2 = 88%), physical function (SMD= -0.82, 95% CI -1.09 to -0.55, P < 0.00001; I 2 = 94%) and stiffness (SMD= -0.88, 95% CI -1.22 to -0.54, P < 0.00001; I 2 = 95%). These agents were not associated with a significant increase in serious adverse events but were associated with a significant increase in discontinuation due to adverse events, abnormal peripheral sensations and peripheral neuropathy. Conclusion   Anti-NGF antibodies appear very promising with regard to alleviating osteoarthritic hip/knee pain but more studies are needed to determine the optimal dosage and the overall risk-to benefit ratio, particularly with long-term use. Disclosure   J. Rammanohar: None. J. Sutton: None. K. Seah: None. W.S. Khan: None. K. To: None.